VLSI Architectures for Future Video Coding - Martina, Maurizio, 1975- (Materials, circuits and devices series, 2019)
This book examines future video coding from the perspective of hardware implementation and architecture design. The book identifies challenges in deploying VLSI architectures for video coding and postulates potential solutions with reference to recent research.